Teaching Decision Making Method in Engineering Exploration Course-An Experience - Kittur, Javeed; Kavale, Sanjeev M. (Journal of Engineering Education Transformations, 2016)
This paper presents the experience of teaching decision making method in Engineering Exploration course. This course is offered to the freshman engineering students of all engineering disciplines. The motivation of including this topic in the curriculum of the course Engineering Exploration is to make the students have hands - on experience in using the decision making method as and when required. In order to obtain a best solution for a given problem knowing and applying decision making process is very important. The decision making method is taught using an activity to the students. Later, an assessment is conducted on applying the learning from the previous activity on decision making. The parameters of assessment focused in this activity are selection of criteria, design features and prioritization. The outcome of the assessment activity clearly shows a good attainment of the two parameters i.e., selection of criteria and prioritization. The other parameter which is design features needs improvement.